Intelligent failure connection algorithm for detecting internet worms - M. Rasheed, Mohammad; Md Norwawi, Norita; Ghazali, Osman; M. Kadhum, Mohammed (Dr. Sang H. Lee, 2009)
Morris worm showed the Internet community for the first time in 1988 that a worm could bring the Internet down in hours.Worm requires host computer with an address on the Internet and any of several vulnerabilities to create a big threat environment.We propose intelligent early system detection mechanism for detecting internet worm.The mechanism of our technique is concerned with detecting the internet worm and stealthy internet worm.The average of failure connections by using Artificial Immune System (AIS) is the main factor that our technique depends on in detecting the worm. In this paper, we show that our algorithm can detect new types of worms. This paper shows that intelligent Failure Connection Algorithm (IFCA) operation is faster than traditional algorithm in detecting worms.